Regulatory challenges and global trade implications of genome editing in agriculture - Fernández Ríos, Danilo; Quintana, Silverio Andrés; Gómez Paniagua, Pilar; Arrúa, Andrea Alejandra; Brozón, Gustavo René; Bertoni Hicar, Moises Santiago; Castro Alegría, Andrés; Goberna, María Florencia (Frontiers in Bioengineering and Biotechnology, 2025)
Genome editing revolutionized agriculture by improving crop productivity, disease resistance, and adaptation to adverse climatic conditions. However, it has faced significant regulatory challenges due to divergent regulations between regions. Although Europe classified these organisms as genetically modified organisms, Africa, Asia, and Latin America implemented more flexible regulatory frameworks, which encouraged innovation and the participation of small companies. These differences could generate high costs, delays in commercialization, and difficulties in product traceability, affecting research and development decisions. This article analyzes the main regulatory challenges and their impact on global trade, proposing strategies for regulatory harmonization to promote transparency, reduce trade barriers, and maximize the potential of these technologies in the face of global challenges such as food security and climate change.